The Stroke-Induced Blood-Brain Barrier Disruption: Current Progress of Inspection Technique, Mechanism, and Therapeutic Target - Okada, Takeshi; Suzuki, Hidenori; Travis, Zachary D.; Zhang, John H. (Current Neuropharmacology, 2020)
Stroke is one of the leading causes of mortality and morbidity worldwide. The bloodbrain barrier (BBB) is a characteristic structure of microvessel within the brain. Under normal physiological conditions, the BBB plays a role in the prevention of harmful substances entering into the brain parenchyma within the central nervous system. However, stroke stimuli induce the breakdown of BBB leading to the influx of cytotoxic substances, vasogenic brain edema, and hemorrhagic transformation. Therefore, BBB disruption is a major complication, which needs to be addressed in order to improve clinical outcomes in stroke. In this review, we first discuss the structure and function of the BBB. Next, we discuss the progress of the techniques utilized to study BBB breakdown in in-vitro and in-vivo studies, along with biomarkers and imaging techniques in clinical settings. Lastly, we highlight the mechanisms of stroke-induced neuroinflammation and apoptotic process of endothelial cells causing BBB breakdown, and the potential therapeutic targets to protect BBB integrity after stroke. Secondary products arising from stroke-induced tissue damage provide transformation of myeloid cells such as microglia and macrophages to pro-inflammatory phenotype followed by further BBB disruption via neuroinflammation and apoptosis of endothelial cells. In contrast, these myeloid cells are also polarized to anti-inflammatory phenotype, repairing compromised BBB. Therefore, therapeutic strategies to induce anti-inflammatory phenotypes of the myeloid cells may protect BBB in order to improve clinical outcomes of stroke patients.
Keywords: microglia